2020
DOI: 10.1002/acm2.13007
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of using Stereotactic Field Diode for field output factors measurement and evaluating three new detectors for small field relative dosimetry of 6 and 10 MV photon beams

Abstract: This study assesses the feasibility of using stereotactic field diode (SFD) as an alternate to gaf chromic films for field output factor (FF) measurement and further evaluating three new detectors for small field dosimetry. Varian 21EX linear accelerator was used to generate 6 and 10 MV beams of nominal square fields ranging from 0.5 × 0.5 cm2 to 10 × 10 cm2. One passive (EBT3 films) and five active detectors including IBA RAZOR diode(RD), SFD, RAZOR nanochamber (RNC), pinpoint chamber (PTW31023), and semiflex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The Razor correction factors showed a larger range of disagreement with the literature than the microSilicon. The largest difference was 2.9% to Gul et al 9 . for a 0.5 × 0.5 cm 2 field size.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…The Razor correction factors showed a larger range of disagreement with the literature than the microSilicon. The largest difference was 2.9% to Gul et al 9 . for a 0.5 × 0.5 cm 2 field size.…”
Section: Discussionmentioning
confidence: 66%
“…The microSilicon correction factors for 6-MV show a maximum difference of 1.6% for a 0.5 × 0.5 cm 2 field size to Schönfeld et al 3 and less than 0.7% to all field sizes of Weber et al 5 The Razor correction factors showed a larger range of disagreement with the literature than the microSilicon. The largest difference was 2.9% to Gul et al 9 for a 0.5 × 0.5 cm 2 field size. Our correction factors agreed more closely with Caser et al, 8 with agreement ranging between −1.5% and 2.0%.…”
Section: Correction Factorsmentioning
confidence: 66%
See 3 more Smart Citations